THEUSEOFPROCESSOR COMPLETED WITHZEOLIT ASBIOFILTER MEDIA TO IMPROVE THE QUALITY OF PALM OIL INDUSTRIAL LIQUID WASTE BASED AMMONIA AND TSS CONCENTRATION - Lilis Elizabet; Budijono '; M Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from January until August 2015 at palm oil industry of PT. PN V Sei. Galuh Tapung Districk Kampar Regency. This study aims to improve the effectiveness of biofilter zeolite with 3 units of the anaerobic process - 2 units aerobic process in reducing the organic pollutants contained in palm oil industry wastewater as a mediafor aquaculture fish. During the study, sampling performed 5 times with intervals of taking for 2 weeks. Based on the results of the study, the biofilter reactor can reduce organic pollutants in wastewater viewed by a decrease in TSS value of 750 mg / L (inlet) to 26.7 mg / L (outlet) with effectiveness of 96.44% (already meet the standard quality standard) and the ammonia concentration of 138.3 mg / L (inlet) to 24.83 mg / L (outlet) with 82.05% effectiveness (not in accordance with the quality standards) with the survival percentage of 50% carp, tilapia 60% and catfish 80%.Key word : Biofilter, TSS, Ammonia, zeolit, palm oil industry wastewater, aquaculture fish.